Anatomical site variations in healing of pediatric femoral shaft fractures: ultrasound evaluation of conservative treatment - Li, Xiang; Song, Junxia; Zhang, Yuan; Wu, Jun; Liu, Xing (Frontiers in Pediatrics, 2026)
ObjectiveUltrasonography is a new alternative to conventional x-ray in fracture examination that avoids radiation damage, but it is unclear whether it can assess fracture healing in children. In this study, we propose to utilize Color Doppler ultrasound to examine in conservative treatment for pediatric femoral shaft fractures, aiming to determine whether there were differences in bone healing at different diaphyseal sites, thereby clarifying the value of ultrasound in fracture healing assessment.MethodsWe performed a prospective observational study to investigate children with femoral shaft fractures treated conservatively who were admitted to our hospital from March 2017 to December 2021. All cases were divided into three groups according to the site of the fracture: upper, middle, and lower segments, and the children were followed-up and observed using Color Doppler ultrasound at the 1st, 2nd, 3rd, and 4th weeks after the injury, recorded the callus-to-femur width ratio (callus thickness/femur width, cm/cm), callus growth rate (callus thickness/days, cm/d), and vascular Resistive Index (RI) and compared the fracture recovery between the groups.ResultsThis study included 31 males and 12 females, for a total of 43 children with femoral shaft fractures. The results showed no statistical difference in callus-to-femur width ratio (cm/cm), callus growth rate (cm/d), and vascular Resistance Index (RI) detected at different fracture sites at the same time after injury (p > 0.05). However, we found that the RI were smaller in the group with faster callus growth rate (cm/d) and vice versa. In addition, when examined at different time, there were statistical differences in the callus-to-femur width ratio (cm/cm), callus growth rate (cm/d), and RI between the different time groups (p < 0.05), and as the time after injury increased, the callus growth rate (cm/d) gradually became slower and the RI value gradually decreased.ConclusionThese results indicate that children with femoral shaft fractures at different anatomical sites demonstrated comparable recovery rates during the early 4-week healing period under conservative treatment, and Color Doppler ultrasound can monitor the recovery process and effectively evaluate bone callus growth by detecting the blood supply around the edge of the fracture.